Engineering interventions in automotive maintenance, repair and operations (MRO) - Chuikov, Stanislav (Global Prosperity, 2026)
Abstract. This article investigates the gap between idealized OEM maintenance schedules and the harsh reality of machinery operation under continuous “24/7” cycles. Based on a retrospective analysis of Big Data covering a 15-year operational history of 350 units of equipment operated at the critical infrastructure facility - separate subdivision “Svitlichanske Regional Utility Enterprise “Luhanskvoda”, the study demonstrates the failure of linear mileage-based maintenance planning. The paper details the physics of “stationary depletion”, where machinery wears out without movement and introduces the author`s proprietary “Chuikov Adaptive Maintenance Framework (CAMF)” for converting engine hours into equivalent mileage. Special attention is paid to the evolution of diagnostics: from simple error code reading to the creation of a “digital shadow” of the aggregate and the implementation of methods analogous to medical diagnostics - spectral analysis of the machine`s “blood” (oil) and listening to its “pulse” (vibroacoustics). The article also reveals non-obvious factors of resource reduction, such as hydraulic heat saturation, vibration resonance of attachment and the managerial phenomenon of “lack of ownership” in shift work. As a solution, a complex of engineering interventions (wear mitigation) is proposed: from the implementation of “kidney loop” oil filtration and cavitation control to surface shot peening. The result of the work is the justification that a modern mechanical engineer must manage the physicochemical processes of material degradation, relying on digital analytics to minimize the Total Cost of Ownership (TCO).